The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1590/s1516-8913201500453
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of a Colombian Spodoptera frugiperdaNucleopolyhedrovirus with Eudragit® S100 by spray drying

Abstract: A Colombian Spodoptera frugiperda nucleopolyhedrovirus NPV003 with high potential for the development of an efficient biopesticide was microencapsulated by spray drying with a pH dependent polymer (Eudragit® S100

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The preservation of spherical shape of DSP/CB and DSP/CB-HAp capsules was also achieved by reinforcing of alginate with mineral fillers. Some folds and cavities were observed, as an evidence of unavoidable contraction force and polymer viscosity increase during any drying process [34]. The rough surface of DSP/CB and DSP/CB-HAp demonstrates the presence and even distribution of mineral fillers.…”
Section: Resultsmentioning
confidence: 99%
“…The preservation of spherical shape of DSP/CB and DSP/CB-HAp capsules was also achieved by reinforcing of alginate with mineral fillers. Some folds and cavities were observed, as an evidence of unavoidable contraction force and polymer viscosity increase during any drying process [34]. The rough surface of DSP/CB and DSP/CB-HAp demonstrates the presence and even distribution of mineral fillers.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments demonstrated that AfMNPV in lignin-based spray-dried formulations had a shelf-life of up to 3 months at 30°C and up to 30 months at 4°C, and with longer residual insecticidal activity in the field compared to unformulated or a glycerin formulation. Camacho et al (2015) improved virus survival in ultraviolet light by preparing microcapsules of the virus with Polyacrylic acid resin, but because of its emulsification, the cost of microencapsulation is too high due to the pollution of oil phase and the complicated impurity removal process.…”
Section: Discussionmentioning
confidence: 99%
“…It loses the significance of keeping a protective UV coating on the virus after spray application. Camacho et al (2015) sprayed drying Eudragit® S100 as a polymer coating to protect viral particles of UVinactivation. Due to the emulsification method, the pollution of a large amount of oil phase during the preparation process and the complicated impurity removal process make the microcapsule process cost too high (Yan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…• Yield (%): the product recovered from each batch was weighed (PCR, Torrey ® , Mexico) and the value was divided among the theoretical weight of the finished product (3.54 kg) to calculate the yield, expressed as a percentage (Camacho et al 2015).…”
Section: Finished Product Characterizationmentioning
confidence: 99%
“…In Colombia, a biopesticide prototype formulated as a wettable powder was developed based on the ErelGV VG010 with mortalities higher than 80% on second and fourth instar larvae (Cuartas et al, 2018). Considering that this biopesticide must be applied on the foliage, the formulation was designed to protect the virus from deleterious conditions that could affect its effectiveness, such as environmental factors (i.e., precipitation, relative humidity, UV radiation, and temperature) (Villamizar et al, 2010;Camacho et al, 2015).…”
Section: Introductionmentioning
confidence: 99%